Fetal Bradyarrhythmias: A Comprehensive Update on Current Knowledge - Maria Elisa Martini Albrecht; Larissa Keren de Azevedo Teixeira; Edward Araujo Júnior; Nathalie Jeanne Bravo-Valenzuela; Roberta Granese (Clinical and Experimental Obstetrics & Gynecology)
Objective: This review aims to improve the accuracy and efficacy of ultrasound diagnosis of fetal bradyarrhythmias. Fetal arrhythmias represent 10% to 20% of referrals to specialized clinics for the evaluation of fetal heart rhythm abnormalities Mechanism: Various methods are available for assessing fetal heart rhythm through ultrasound and fetal echocardiography, which facilitate accurate diagnosis and help determine the optimal management strategies. Despite advancements in diagnostic techniques, the absence of studies with a substantial number of cases has resulted in significant variability in treatment approaches, influenced by local expertise and available resources. Findings in Brief: Fetal bradycardias can be transient or persistent conditions. Differentiating between them is critical for determining appropriate management. Second-trimester physiological transient bradycardia is characterized by temporary decelerations in fetal heart rate that resolve spontaneously to normal rhythm without requiring treatment or follow-up. In contrast, isolated or immune-mediated complete atrioventricular block may progress rapidly to hydrops, requiring close monitoring, medical intervention, and, in some cases, early delivery. Conclusion: In this review, we provide a comprehensive overview of all types of fetal bradycardias and the intrauterine management strategies used for their treatment.